Leonor de Andrade or Francisca Sotelo, bitter paths that lead to the holy office of Lima, 17 th century. - Cordero Fernández, Macarena (Cuadernos de Historia, 2024)
The following article analyzes the feelings of a family, especially those of Leonor de Andrade, mother and wife, who had to face the horror of an inquisitorial process before the of the Holy Office Tribunal of Lima –in the mid-17th century–. Due to her religious identity as a Judaizer, Leonor de Andradre, which constituted a danger, not only due to the heretical nature of her practices and beliefs, but also, that the fact of being a woman was considered, by the Inquisition, as a great threat, because that Moses’ religion was transmitted through women. In such circumstances, Leonor experienced a series of feelings, showing her drive to survive and hope to see her little daughter again. Also, we propose to outline the subjectivities of the Inquisition and some officers from a cultural perspective, given that emotions are practices that redefine the actions of the subjects.